20 Years of insulin lispro in pediatric type 1 diabetes: a review of available evidence. Issue 2 (8th July 2016) - Kaiserman, Kevin; Jung, Heike; Benabbad, Imane; Karges, Beate; Polak, Michel; Rosilio, Myriam
Abstract : Background: Insulin lispro, the first rapid‐acting insulin analog, was developed 20 years ago and has been studied in multiple situations and various populations. Objective: To review the literature on the use of insulin lispro in children, adolescents, and young adults. Patients: Children, adolescents, and young adults with type‐1‐diabetes. Methods: One hundred and twenty‐two relevant publications, identified by a systematic (MEDLINE) and manual literature search, were reviewed. Results: Multiple daily injection (MDI) treatment with insulin lispro or other rapid‐acting insulins, mainly using neutral protamine Hagedorn (NPH) insulin as the basal component, was associated with reduced postprandial glucose excursions, similar or improved HbA1c levels, and similar or reduced risks of severe hypoglycemia when compared with regular human insulin across all age‐groups. Continuous subcutaneous insulin infusion (CSII)‐treatment with insulin lispro also showed similar or improved glycemic control vs. MDI‐ or other CSII‐regimens across all age‐groups, without increasing the rate of severe hypoglycemia. The other two more recently developed rapid‐acting insulins (aspart, glulisine) demonstrated non‐inferiority to lispro on HbA1c. Long‐term observational studies and real‐life experience indicate that the increasing use of optimized MDI‐ and CSII‐regimens with insulin lispro was associated with improvements in overall glycemic control. Conclusions: For almost 20 years, rapid‐acting insulins, in particular insulin lispro as the first‐in‐class, have contributed to broadening the treatment options for the unique needs of pediatric patients with type‐1‐diabetes across all age‐groups, and have enabled more physiological insulin administration. Now widely used, they have allowed pediatric patients to safely reach better glycemic control, with more flexibility in their daily lives.